Board Diversity and Earnings Quality of Listed Deposit Money Banks in Nigeria - Essien, Michael David; Akpan, Dorathy Christopher (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
Investors’ confidence in the financial reporting process has been hampered because of unethical accounting practices and earnings management and this could be as a result of weak governance structures. The main objective of this study therefore was to examine the effect of board diversity on earnings quality of deposit money banks listed on the floor of the Nigerian Exchange Group from 2014-2023. The independent variable of the study was proxied by board age diversity, board experience diversity and board financial expertise, while the dependent variable was proxied by discretionary loan loss provision. The research design adopted for this study was ex post facto because secondary data were used. The sample size of this study was 10 deposit money banks purposively selected. Ordinary least square regression was used to analyze the data used and statistical software package employed was E-view version 10. The findings of the study revealed that board age diversity has a non-significant negative effect on the discretionary loan loss provisions; experience diversity and board financial expertise have significant negative effect on discretionary loan loss provisions of listed deposit money banks in Nigeria. Thus, it was concluded that board diversity has significant influence on earnings quality of listed deposit money banks in Nigeria. Therefore, it was recommended that the management of deposit money banks should prioritize recruiting board members with robust financial background and expertise to enhance both their earnings quality and financial risk management strategies.